2020
DOI: 10.2196/21450
|View full text |Cite
|
Sign up to set email alerts
|

A Cardiovascular Health and Wellness Mobile Health Intervention Among Church-Going African Americans: Formative Evaluation of the FAITH! App

Abstract: Background In light of the scarcity of culturally tailored mobile health (mHealth) lifestyle interventions for African Americans, we designed and pilot tested the Fostering African-American Improvement in Total Health (FAITH!) App in a community-based participatory research partnership with African American churches to promote cardiovascular health and wellness in this population. Objective This report presents the results of a formative evaluation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…In a recent qualitative analysis of the FAITH! app pilot study, participants demonstrated that they received encouragement and social support toward a healthy lifestyle from posts by other participants on the sharing board [ 48 ]. Thus, facilitating opportunities for discussion among study participants through a sharing board feature may foster meaningful engagement in mHealth interventions and increase social support in mHealth lifestyle interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent qualitative analysis of the FAITH! app pilot study, participants demonstrated that they received encouragement and social support toward a healthy lifestyle from posts by other participants on the sharing board [ 48 ]. Thus, facilitating opportunities for discussion among study participants through a sharing board feature may foster meaningful engagement in mHealth interventions and increase social support in mHealth lifestyle interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was co-designed with African American community members from participating churches who could give voice to the daily lived experiences of African Americans to ensure that the intervention emphasized African American faith, spirituality, and social connectedness. This study implemented an mHealth lifestyle intervention that was well-aligned with smartphone use patterns in African Americans and one that was well-received by participants [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 724 veterans with CHD with access to mobile technologies, enrolled in a home-based virtual CR program, there were no differences in CR participation and completion by race [ 83 ]. Additionally, a mobile application that was tailored to African American patient preferences was successful in improving cardiovascular health behaviors [ 84 ]. Future research is needed to refine home-based CR to include technology that is accessible and tailored to African Americans and other minority patients.…”
Section: Novel Cr Delivery Modalitiesmentioning
confidence: 99%
“…10 , 11 Thus smartphone-based lifestyle interventions can be effective platforms to address these CVH disparities in AAs, but require the use of a community-engaged, and user-centered approach to develop successful interventions. 9 , 12 14 There has been a lag in the widespread adoption of evidence-based, community-based participatory research (CBPR) approaches to build equitable community–academic partnerships with AA communities. These approaches have been shown to be effective in recruiting historically underrepresented and marginalized racial/ethnic minority groups into clinical research using culturally tailored recruitment strategies.…”
Section: Introductionmentioning
confidence: 99%